Motivation to Read and Parental Support: Implications to the Grade Six Student’s Reading Comprehension (British Journal of Multidisciplinary and Advanced Studies, 2023)
Any Filipino child with sufficient reading motivation and parental support would have greater chances of success in school. This descriptive correlational study sought to determine if there is an association among the participants’ reading comprehension level, their level of motivation to read, and the extent of their parents’ support in reading. Fifty (50) Grade 6 pupils from a public school in the division of Misamis Oriental were the participants. Researcher-made and validated instruments were utilized to gather the data. The research instruments were pilot tested on 30 pupils in a nearby school which yielded reliable results in terms of its Cronbach Alpha. Descriptive statistics and Spearman Rho were used to analyze the gathered data. The study revealed that the participants’ level of motivation to read and the extent of their parental support were generally high. The reading comprehension level in all components, identifying the main idea and key details, sequencing a passage into an ordinal series, making inferences, and identifying unfamiliar vocabulary was fair. Data also showed that the participants’ motivation for reading and the extent of parental support is not significantly associated with their reading comprehension skills. The results point to the need for teachers and educational leaders to design appropriate, effective, and research-based interventions to arrest the low reading comprehension performance of the students.